Pengembangan Media Pembelajaran Berbasis Articulate Storyline 3 pada Pembelajaran Pendidikan Agama Islam di SDN 10 Pasaman - Zeni Nur Impiyani; Siska Yulia Rahmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low use of interactive learning media in Islamic Religious Education (PAI) learning at SDN 10 Pasaman, where the learning process is still conventional and lacks active student involvement. This condition results in low student interest and engagement in understanding the learning material. Therefore, this study aims to develop an Articulate Storyline 3-based learning media that is attractive, interactive, and feasible to improve students’ interest and understanding of Islamic Religious Education materials, particularly the topic of faith in the messengers of Allah. This research is a Research and Development (R&D) study using the Four-D (4D) development model, which includes the stages of define, design, develop, and disseminate. However, this study is limited to the develop stage. The define stage involved analyzing needs, curriculum, student characteristics, and learning materials. The design stage included media planning, material preparation, storyboard development, and research instrument preparation. The develop stage was conducted through validation by material experts, media experts, and language experts, followed by product revision based on validator suggestions and field trials to determine the practicality level of the media. The results indicate that the Articulate Storyline 3-based learning media is categorized as very valid based on expert validation. The material expert validation obtained an average score of 4.88 (very valid), media expert validation 4.96 (very valid), and language expert validation 4.96 (very valid). Field trial results showed that the practicality level based on student responses was 89.4% (very practical), while teacher responses reached 84.44% (very practical). These findings indicate that the developed media is feasible, practical, and easy to use in learning. Therefore, this learning media is recommended as an alternative interactive medium for Islamic Religious Education in elementary schools and can be further developed for other materials or educational levels.